Geologia, controle estrutural e regime de fluídos da mineralização aurífera da Fazenda Figueira Branca, Terra Nova do Norte / MT - Lima Junior, Max Salustiano de (2017)
The gold deposits of Figueira Branca Farme are located in the eastern portion of the Alta Floresta Gold Province (Dardene & Schobbenhaus, 2001), south central Amazon Craton, in the Tapajós-Parima Province (2.1-1.87 Ga) The mineralization is housed in 1st and 2nd order structures related to a transpressive shear system imposed on granite rocks of U-Pb of 1.88 Ga, which evolved in a shallow crustal environment, forming a conjugated failure / fracture system. There are two main systems of veins found: SV1, hosting deposits of sulfide, fractured and recrystallized veins, filling fault-like structures with directions N80 ° W; and SV2, harboring veins with free gold, preserving comb textures, crustiform and breccias, which fill extension structures, with directions N05 ° - 15 ° E. The nucleation of hydrothermal alterations, distal potassium, and chlorite and seriytic proximal changes, which envelop the SV1 and SV2 veins, vary from centimeter to tens of meters indicating fluid / rock interaction. Being the main gold mineralization associated with the veins systems, and being subordinately disseminated in the hydrothermalized rock. Results of fluid inclusions analysis indicate the presence of carbonic (T1), aquocarbonic (T2), saturated (T3) and unsaturated (T4) saline coexistence inclusions formed in a homogenization range between 100-300 ° C and eutectic at -10 ° C, -22 ° C, -30 ° C, -38 ° C and -52 ° C; modeling chlorocarbon and saline, chlorinated systems rich in K, Mg, Fe and Ca, in addition to NaCl and water, with salinities of 0 to 40% equiv. NaCl. It is suggested that these fluids originated through the cooling of granite domes, assisted by shear systems at shallow crustal levels; where they would interact with meteoric circulation fluids, as shown by the oxygen isotope results for SV2 (18O H2O 18O between -0.1 and 5.7). In this case the gold mineralization is attributed to Faz. Figueira Branca, to Intrusion Related deposit models, with pyrite as the dominant sulfide. While the granitic and volcanic rocks occur in this region of Figueira Branca Farm, previously mapped as SI Matupá 2 (granites) and Colíder Suite (Volcanic), provided ages (U-Pb) of 1.88 Ga and 1.89 Ga, respectively. Thus according to the ages and the circumscribed nature of the granitic body we chose to call it Figueira Branca Granite for the granites, and it is possible to correlate the volcanic ones to the Iriri Group. These data open a window for the correlation between the Tapajós and Peixoto domains of Azevedo, strengthening the thesis that both domains had a similar evolution, having as base the Complex Cuiú-Cuiú.